Semi-automated mid-turbinate swab sampling using a six degrees of freedom collaborative robot and cameras - Leung, Michael; Ortiz, Ricardo; Jo, Bruce W. (Institute of Advanced Engineering and Science, 2023)
Mid-turbinate swab sampling is an effective way to detect the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. Several articles discussed the importance and benefits of using robotic technology to alleviate healthcare workers’ daily burdens against coronavirus disease 2019 (COVID-19). Therefore, a semi-automated approach for collecting swab samples from the mid-turbinate area-approximately 4 cm inside the nose is proposed. The system utilizes a six-degrees-of-freedom (6-DOF) Doosan Robot M1509 and two smart visual sensors: one on the end effector and the other fixed to the side for estimating the angle of the nasal path. This work suggests a method of robot and human collaboration in the sampling process that could minimize infections from samplings and guarantee uniformly administered sampling processes. The effectiveness of this proposed work was tested on a live patient and a phantom head; meanwhile, the insertion process was only administered on the phantom head. Although the overall time of the experiment was greater than a manual swab, the feasibility of implementing robotic applications for COVID-19 swab sampling has been practically showcased in this paper.